1986
DOI: 10.1002/j.1551-8833.1986.tb05681.x
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Contamination of a Preoperational Treatment Plant

Abstract: A study of the distribution of Legionella in a newly constructed water treatment facility found Legionella pneumophila (serogroup 1) in both hot‐ and cold‐water lines. The contamination was monitored by bacterial enumeration of samples collected from various sites in the building and from disassembled plumbing fixtures. Repeated flushing and hyperchlorination were inadequate as decontamination procedures, presumably because the organism had colonized interior spaces of valves and associated parts that are inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, it was not possible to demonstrate the presence of the organisms in the boosted mains supply during the course of this investigation and the apparent elimination of the organism from the plumbing system for 20 weeks after chlorination was not indicative of low level seeding from the mains supply. Although the role of the booster pumps as an amplification site could not be demonstrated, the temperature profile of the water was within the range which permits legionella colonization (Voss et al 1986).…”
Section: Discussionmentioning
confidence: 92%
“…However, it was not possible to demonstrate the presence of the organisms in the boosted mains supply during the course of this investigation and the apparent elimination of the organism from the plumbing system for 20 weeks after chlorination was not indicative of low level seeding from the mains supply. Although the role of the booster pumps as an amplification site could not be demonstrated, the temperature profile of the water was within the range which permits legionella colonization (Voss et al 1986).…”
Section: Discussionmentioning
confidence: 92%
“…Although legionellae were not isolated from water before it entered either hospital property, periodic sampling would be needed to rule out intermittent entry of legionellae from outside sources such as municipal water reservoirs. Legionellae have been isolated from water treatment plants (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The first category (A), potable water outside and on the boundary of hospital property, is included to document external sources of municipal water that contain legionellae and may seed the water and plumbing systems of the building. The reports of other investigators such as Voss et al (17,18) have indicated that municipal water treatment plants harbor legionellae and emphasize the need to identify external contamination sources. The second category (B), the general potable water system for a hospital or facility, includes sites that can be very important for disease transmission.…”
mentioning
confidence: 99%
“…Since 1985, studies have shown that Legionella is present in all segments of community water supplies, including treatment facilities. 5,6,7,8 The 1985 Legionella Criteria Document states that Legionella is widely distributed in the natural environment worldwide. 9 Legionella exhibits the ability to survive in an extremely wide range of conditions in natural and man-made aquatic habitats.…”
Section: Why More Uniform Regulation Is Neededmentioning
confidence: 99%